STABILITY CHARACTERISTICS OF COMPRESSIBLE BINARY PLANAR JETS - Mendonca, M. T.; Vargas, M. M. (Revista de Engenharia Térmica, 2020)
The present work investigates the stability of compressible binary planar jets. Different from a homogeneous jet, where a single chemical species is present, the binary jet may have strong density gradients due to the choice of the chemical species considered in each stream. The goal is to identify the possible instability modes for simple and co-flowing jets and investigate the effect of density gradients on the flow structure, growth rates, unstable frequency range and disturbance phase speed for each mode. The effect of species concentration on free shear layer stability has been reported previously in the literature, but detailed comparisons between stability modes and characteristics for a range of density ratios typical of oxygen and hydrogen mixtures as well as the identification of inner and outer sinuous and varicose modes are new. Linear stability theory is used to determine the stability characteristics of the different configurations. For the co-flowing jet four different modes are found, the inner and outer shear layers both have sinuous and varicose modes. Both for the sinuous and varicose modes the simple jet is more unstable when the fluid with the highest density is at the inner jet, with amplification rates twice as high as the lowest density ratio considered, but the range of unstable frequencies can be four times lower. The sinuous mode is less dispersive than the varicose and the disturbance speeds may vary by one order of magnitude with density ratio. For co-flowing jets the external mode is up to seven times more unstable, but this is due to the choice of the velocity ratio considered. For the inner mode the density gradient has a stabilizing effect regardless of which species is at the center. The co-flowing jet is more dispersive, except for the varicose inner mode. The variation of phase speed with density gradient is not as strong as in the simple jet. The ratio of larges to lower phase speeds are of the order of 2 for the co-flowing jet and 4 for the simple jet.